2021
DOI: 10.1097/mao.0000000000003134
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Tegmen Tympani Dehiscence: Causes and Treatment of Conductive Hearing Loss

Abstract: Objective:Conductive hearing loss (CHL) commonly arises in patients with spontaneous dehiscence of the tegmen of the temporal bone with meningoencephalocele (SME). The aim of this study was to further investigate 1) the potential mechanisms for CHL in this setting; 2) hearing outcomes following surgery to address SME, and 3) the possible causes of persistent CHL following surgery.Study Design:Retrospective case review.Setting:Tertiary referral center.Patients and Intervention:Seven patients (six female; nine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Heywoody cols. informaron la existencia, en 7 pacientes intervenidos quirúrgicamente de su dehiscencia del tegmen, la presencia en 3 de ellos de una dehiscencia del canal semicircular superior asociada (43%) 29 . Castellucci y cols.…”
Section: Resultsunclassified
“…Heywoody cols. informaron la existencia, en 7 pacientes intervenidos quirúrgicamente de su dehiscencia del tegmen, la presencia en 3 de ellos de una dehiscencia del canal semicircular superior asociada (43%) 29 . Castellucci y cols.…”
Section: Resultsunclassified
“…Reconstruction of the bony skull base defect has been reported using autologous tissues including cortical bone, cartilage, bone dust, fat, and muscle (18). Allografts such as porous polyethylene (19), titanium mesh (1), and hydroxyapatite cement (3,5,(7)(8)(9)(10)19,20) have also been reported, although some studies have reported increased rates of postoperative infection with allografts (1,19).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports in the literature have suggested that SSCD raises the risk of vestibular injury and resultant sensorineural hearing loss in MF craniotomy (1,10), with some advocating for intraoperative ABR monitoring when SSCD is suspected on preoperative imaging (1). Routine superior canal resurfacing has also been described (3,8) to prevent sensorineural hearing loss, although the practice is not uniformly successful. Manipulation of the ossicles has also been theorized to cause inner ear trauma and postoperative sensorineural hearing loss (8,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations